The Metagenomic Analysis of the Pig Digestive System Microbiome as a Basis for Disease Control on Farming in Tangerang District, Indonesia - Endrakasih, E.; Pazra, D. F.; Wahyuningsih (Faculty of Animal Science, IPB University, 2024)
Characteristics of microbiome of the pig’s digestive tract play an important role in the animal’s physiology, including metabolism, nutrient processing, the body’s immune response, and disease resistance. This study aims to analyze the abundance and diversity of microorganisms (pathogenic and non-pathogenic) from the digestive system of pigs on farms in Tangerang District. The samples used in this research were pig feces from 43 pig farms in Tangerang District. Then DNA extraction was carried out using the Zymo Quick-DNA Fecal/Soil Microbe Kit according to manufacturing procedures. Sequencing was performed using an MGI DNBSEQ-G50 machine with a DNBSEQ-G50RS High-throughput sequencing set (FCL PE100) according to manufacturing procedures. The quality of fastq files was evaluated with FastQC. Taxonomic classification of the processed sequences was performed using Diamond, followed by MEGAN6. The microbiome of the pig’s digestive system was dominated by bacteria (85%) with the taxonomic profile at the phylum level of abundance dominated by Firmicutes (84.46%) and Bacteroidetes (9.11%). Abundance at the genus level was dominated by Enterococcus (20.44%) and Clostridium (10.31%), and at the species level it was dominated by Escherichia coli (4.92%) and Levilactobacillus brevis (4.84%). There were 10 species of pathogenic bacteria detected, with E. coli showing the highest relative abundance (4.92%). Changes in the gut microbiome play an important role in the physiology of animal health and disease. In addition, the pathogenic bacteria detected not only affect the health and productivity of pigs but also have the potential to threaten public health.